2000
DOI: 10.1508/cytologia.65.253
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic Relationship between Akodon azarae and A. boliviensis (Rodentia, Sigmodontinae).

Abstract: Summary The genus Akodon, comprising more than 60% of the species of the Akodontini, widely distributed in South America, presents many interesting cytogenetic atributes, such as an ample karyotypic variation (2n=10-52), intraspecific and intrapopulational polymorphisms of the autosomes and of the gonosomes, and, as in both species here studied, XY fertile females. We report a cytogenetic comparative study of A. azarae (2n=38) and of A. boliviensis (2n=40) specimens. In these species, only the sex chromosomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The long arm of pair 1 of A. dolores, considered to be homologous to pair 1 of A. boliviensis and A. azarae (Bianchi and Merani, 1984;Lisanti et al, 2000), did not exhibit the proximal IT observed in these chromosomes (the short arm is not conserved in these species). A more detailed analysis of the Gbanding patterns (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The long arm of pair 1 of A. dolores, considered to be homologous to pair 1 of A. boliviensis and A. azarae (Bianchi and Merani, 1984;Lisanti et al, 2000), did not exhibit the proximal IT observed in these chromosomes (the short arm is not conserved in these species). A more detailed analysis of the Gbanding patterns (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…1A, B). This chromosome pair is represented by two telocentric pairs in A. boliviensis and A. azarae, among several akodontine species (Bianchi and Merani, 1984;Lisanti et al, 2000). Comparison of the G-banding patterns did not reveal any rearrangement corresponding to this interstitial signal (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation